(untitled) (Slavic Studies, 2024)
The paper analyzes Macedonian and Croatian phytonymic phraseological expressions that are related to the concept of success and failure. The phraseological material on which the research was done is phraseographic – the phraseological expressions are excerpted from the Phraseological Dictionary of the Macedonian language and from the Croatian Phraseological Dictionary. Before the start of the research, the hypotheses were given, which was followed by semantic-conceptual analysis and interlinguistic equivalence analysis of the phraseological material. The aim of the research is to contribute to the study of phraseology of the Macedonian and Croatian language, as well as to the contrastive phraseology of these two languages.